Ultrasonic flow measurement under non-standard conditions. Analysis of the influence of basic hydraulic elements disturbing the flow on the measurement result - Piechota, Piotr; Synowiec, Piotr; Wędrychowicz, Wiesław; Wróblewska, Elżbieta; Andruszkiewicz, Artur (Instal, 2023)
The article deals with flow velocity measurements using the ultrasonic method under non-standard conditions. The paper analyzes the effect of flow disturbance obstacles, in the form of common flow system components: knife gate valve, butterfly valve and hydraulic elbow, on the errors of ultrasonic velocity measurements made at varying distances from the disturbance component. The results of measurements made behind the obstruction were compared with those made with a reference flow meter on a straight section of the pipeline in front of the obstruction. This made it possible to assess the influence of obstacles causing disturbance and changes in the distribution of flow velocity on the measured value of velocity. In industrial conditions, it is often impossible to make a measurement with the straight sections of the pipeline from the obstacle, as specified in the standards. Knowledge of the effect of basic types of hydraulic elements on flow meter readings when measurements are made without maintaining the required straight pipeline sections can be used practically to assess the feasibility of the measurement and evaluate the reliability of the results obtained.
Keywords: ultrasonic flowmeter; flow measurement; measurement accuracy; hydraulic elbow; knife gate valve; butterfly valve